Drug utilization pattern of analgesics in various departments of a tertiary care teaching rural dental hospital - Patel, Nirav N.; Soitawala, Sunil; Mark, Andrew; Desai, Haresh (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The aim was to study drug utilization pattern of analgesics in various departments of a tertiary care teaching rural dental hospital. Methods: A prospective and observational study was undertaken in 150 patients from January 2014 to February 2014. Relevant information was obtained from the interview as well the hospital case record. Structured and pre-tested format were used for compiling the data. Results: The majority of the patients (46%) were in the age group 41-60 years. Common indications for analgesic use included endodontic diseases (61.3%), surgical procedures (41.33%), and periodontal diseases (27.33%). Three analgesic formulations were used leading to a total of 150 drug uses. Fixed-dose drug combination (FDC) of diclofenac sodium plus paracetamol (78.66%) was the most commonly prescribed analgesic formulation, followed by aceclofenac plus paracetamol (15.33%) and ibuprofen (6%). The average number of analgesics prescribed per patient was 1.94. Analgesics were prescribed for 3 days. Except ibuprofen, FDC of diclofenac sodium + paracetamol and aceclofenac + paracetamol have been included in the WHO model list of essential medicines. All analgesic drug formulations were prescribed by their brand names. Conclusions: Drug utilization data can help to formulate appropriate clinical guidelines for drug use and facilitate rational use of medicines in population.